Prognosis of upstaged N1 and N2 disease after curative resection in patients with clinical N0 non-small cell lung cancer - Park, Jae Kil; Moon, Youngkyu (Journal of Thoracic Disease; Vol 11, No 4 (April 30, 2019): Journal of Thoracic Disease, 2019)
Background: Nodal upstaging occasionally occurs after curative resection in clinical N0 non-small cell lung cancer (NSCLC). The purpose of this study was to evaluate the prognosis of clinical N0 NSCLC (T1–2, tumor size 5 cm or smaller) after upstaging to pathologic N1 or N2. Methods: From 2005 to 2015, 676 consecutive patients were diagnosed with clinical T1–2N0 NSCLC and underwent curative resection. Among these, tumors were upstaged to N1 in 46 patients and to N2 in 24 patients. We analyzed the prognosis of upstaged tumors. For comparison of prognosis between nodal upstaging groups and others in the same stage, patients with preoperative pathologically proven N1 (n=31) and N2 (n=55) NSCLC were included in the study. Results: A total of 70 patients (10.4%) had nodal upstaging after curative resection of clinical N0 NSCLC. Upstaging to N1 occurred in 46 patients and upstaging to N2 occurred in 24 patients. The 5-year disease-specific survival rate was not statistically different between the upstaged and non-upstaged N1/N2 groups in N1 disease (73.3% vs. 70.5%, P=0.247) or in N2 disease (58.9% vs. 50.7%, P=0.283). Multivariate analysis showed that nodal upstaging was not a significant prognostic factor in N1 or N2 NSCLC (hazard ratio =0.385, P=0.235; hazard ratio =0.677, P=0.458). Conclusions: Postoperative nodal upstaging from clinical T1–2N0 NSCLC was not a significant prognostic factor in the same stage. Therefore, surgical treatment of clinical T1–2N0 lung cancer diagnosed by imaging without preoperative pathologic lymph node staging can be a treatment option.